The next time you get stuck with algebra 2 problems or just can’t figure out an equation, log-on to one of the several math help websites and access algebra 2 help online. Fast becoming one of the easiest ways to get tutoring help, online algebra 2 help is great for students, since its there any time they need it. Algebra 2 online help has great math solvers who explain well and solve problems with students so that they understand the steps.

## Online Algebra 2 Help

Students will find that online help gives them a lot of flexibility in terms of time and place. Whatever time of the day or night you need help, you will find it online. Use algebra 2 online help to practice what you learn with the hundreds of practice worksheets and problems. Many are available with the answers so that you can correct your work by yourself. Don’t worry about exams again as you can simply log-on to online algebra 2 exam prep and get great pointers to help you score well in your exams. Try online algebra 2 help and join hundreds of students as they discover an innovative way to learn.

## Solved Examples

**Question 1:**Simplify $\frac{x^2 - x - 2}{x^2 - 4}$

**Solution:**

Given, $\frac{x^2 - x - 2}{x^2 - 4}$

Step 1:

Factorized polynomials:

x

= x(x - 2) + (x - 2)

= (x + 1)(x - 2)

and x

= (x - 2)(x + 2)

Step 2:

$\frac{x^2 - x - 2}{x^2 - 4}$ = $\frac{(x + 1)(x - 2)}{(x - 2)(x + 2)}$

= $\frac{x + 1}{x + 2}$

=> $\frac{x^2 - x - 2}{x^2 - 4}$ = $\frac{x + 1}{x + 2}$

Step 1:

Factorized polynomials:

x

^{2}- x - 2 = x^{2}- 2x + x - 2= x(x - 2) + (x - 2)

= (x + 1)(x - 2)

and x

^{2}- 4 = x^{2}- 2^{2}= (x - 2)(x + 2)

Step 2:

$\frac{x^2 - x - 2}{x^2 - 4}$ = $\frac{(x + 1)(x - 2)}{(x - 2)(x + 2)}$

= $\frac{x + 1}{x + 2}$

=> $\frac{x^2 - x - 2}{x^2 - 4}$ = $\frac{x + 1}{x + 2}$

**Question 2:**Sasra is three times as old as her son. Five years later, she will be two and a half times as old as her son. How old she is and her son.

**Solution:**

Let present age of Sasra's son = x

Then age of Sasra = 3x

Age of Sasra's son = x + 5

and age of Sasra = 3x + 5

Since she will be two and a half times as old as her son:

=> 3x + 5 = $2\frac{1}{2}$(x + 5)

=> 3x + 5 = $\frac{5}{2}$(x + 5)

=> 2(3x + 5) = 5(x + 5)

=> 6x + 10 = 5x + 25

=> 6x - 5x = 25 - 10

=> x = 15, age of Sasra's son

So age of Sasra = 3x = 3 * 15 = 45

Then age of Sasra = 3x

5 years later :5 years later :

Age of Sasra's son = x + 5

and age of Sasra = 3x + 5

Since she will be two and a half times as old as her son:

=> 3x + 5 = $2\frac{1}{2}$(x + 5)

=> 3x + 5 = $\frac{5}{2}$(x + 5)

=> 2(3x + 5) = 5(x + 5)

=> 6x + 10 = 5x + 25

=> 6x - 5x = 25 - 10

=> x = 15, age of Sasra's son

So age of Sasra = 3x = 3 * 15 = 45

**She is 45 years old and her son is 15 years old.**

Answer:Answer:

**Question 3:**If the numerator of a fraction is increased by 2 and the denominator by 1, it becomes $\frac{5}{8}$ and if numerator and denominator are increased by 1 each, the fraction becomes equal to half. Find the fraction.

**Solution:**

Step 1:

Let the fraction will be $\frac{x}{y}$

Case 1:

Increased numerator by 2 and denominator by 1, it becomes $\frac{5}{8}$

=> $\frac{x + 2}{y + 1}$ = $\frac{5}{8}$ .......................(1)

Case 2:

Increased numerator and denominator by 1, the fraction becomes equal to half

=> $\frac{x + 1}{y + 1}$ = $\frac{1}{2}$ .........................(2)

Step 2:

(1) => 8(x + 2) = 5(y + 1)

=> 8x + 16 = 5y + 5

=> 8x - 5y + 11 = 0 .............................(3)

(2) => 2(x + 1) = y + 1

=> 2x + 2 = y + 1

=> 2x - y + 1 = 0

=> y = 2x + 1 ...............................(4)

Step 3:

Put y = 2x + 1 in equation (3)

=> 8x - 5(2x + 1) + 11 = 0

=> 8x - 10x - 5 + 11 = 0

=> -2x + 6 = 0

=> 2x = 6

=> x = 3

Step 4:

Put x = 3 in equation (4)

=> y = 2 * 3 + 1

=> y = 7

Hence the fraction is $\frac{3}{7}$.

Let the fraction will be $\frac{x}{y}$

Case 1:

Increased numerator by 2 and denominator by 1, it becomes $\frac{5}{8}$

=> $\frac{x + 2}{y + 1}$ = $\frac{5}{8}$ .......................(1)

Case 2:

Increased numerator and denominator by 1, the fraction becomes equal to half

=> $\frac{x + 1}{y + 1}$ = $\frac{1}{2}$ .........................(2)

Step 2:

(1) => 8(x + 2) = 5(y + 1)

=> 8x + 16 = 5y + 5

=> 8x - 5y + 11 = 0 .............................(3)

(2) => 2(x + 1) = y + 1

=> 2x + 2 = y + 1

=> 2x - y + 1 = 0

=> y = 2x + 1 ...............................(4)

Step 3:

Put y = 2x + 1 in equation (3)

=> 8x - 5(2x + 1) + 11 = 0

=> 8x - 10x - 5 + 11 = 0

=> -2x + 6 = 0

=> 2x = 6

=> x = 3

Step 4:

Put x = 3 in equation (4)

=> y = 2 * 3 + 1

=> y = 7

Hence the fraction is $\frac{3}{7}$.